2020
DOI: 10.1007/s11356-020-10097-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial structure and diversity in non-sanitary landfills and association with physicochemical parameters

Abstract: This study assessed the bacterial populations in a non-sanitary landfill around Guarani Aquifer recharge zone in Brazil. Samples from two different positions (sites 1 and 2) at three different depths were evaluated, totaling six solid waste samples; two samples from an impacted stream were also collected. 16S rRNA sequencing was performed using the Ion S5TM XL platform; 3113 operational taxonomic units (OTUs) and 52 phyla were identified. Proteobacteria (37%) and Firmicutes (28%) were the most abundant phyla i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Similarly, the genus Gelria has been reported as in the metabolism of fatty acids, in the nal stages of fermentation (Fitzgerald et al, 2019) and in reducing land ll zones with higher organic matter and K content (Morita et al, 2020c). This genus was more abundant in samples located in capped zones and in F12, showing its greater relevance in methanogenic conditions.…”
Section: Taxonomic Analysis At the Level Of Generamentioning
confidence: 77%
“…Similarly, the genus Gelria has been reported as in the metabolism of fatty acids, in the nal stages of fermentation (Fitzgerald et al, 2019) and in reducing land ll zones with higher organic matter and K content (Morita et al, 2020c). This genus was more abundant in samples located in capped zones and in F12, showing its greater relevance in methanogenic conditions.…”
Section: Taxonomic Analysis At the Level Of Generamentioning
confidence: 77%
“…Proteobacteria was the most abundant group in both landfill samples, and was overwhelmingly abundant in the SZ landfill (67.59%) (Figure 2a). A high abundance of Proteobacteria was previously found in landfills [28][29][30], which could play a vital role in organic matter degradation [28]. For instance, Zainun et al [29] found that Proteobacteria were predominant in both active and closed non-sanitary landfills, and within this phylum, Gammaproteobacteria were the most abundant class detected in the active landfill, indicating their potential role in the decomposition of organic matter.…”
Section: Microbial Taxonomy Composition At the Phylum Levelmentioning
confidence: 92%